THE IMPORTANCE OF HR 4.0 IN CONTEMPORARY ORGANIZATIONS - da Silva, Julia Chan Novais Carneiro; Serrano, Cristiane de Oliveira; da Costa, Elvio Carlos (Revista Interface Tecnológica, 2022)
This article aimed to deepen the concept of HR 4.0 in order to identify, analyze and understand the challenges encountered by the sector, seeking to know the new People Management and bring the definition, changes and challenges, in addition to knowing how the current HR 4.0 meshes. With the role of leadership in this new scenario. The methodology is based on bibliographic research, using two databases: Scielo and Capes journals, in order to identify the work already undertaken in this area. The results were presented in three categories of analysis: 1) The RH 4.0 paradox; 2) Challenges in implementing HR 4.0 and its impact on companies and 3) Competencies of a manager. It was found that in this new look at HR, people are considered essential for the functioning of an organization and above all how fundamental it is for managers to develop hard and soft skills to act in the transformations and changes of contemporary organizations.
Keywords: Fourth Revolution; HR 4.0; Leadership; Technologies; Skills